Evaluating firm resilience through responsiveness and logistics outsourcing in the COVID-19 era - Laari, Sini; Rintala, Oskari; Töyli, Juuso; Solakivi, Tomi; Ojala, Lauri (Emerald, 2025)
Purpose: This paper aims to investigate how firms can enhance their resilience in response to the disruptions caused by the COVID-19 pandemic. Specifically, the study focuses on assessing responsiveness as an antecedent and logistics outsourcing as a boundary condition to resilience.
Design/methodology/approach: Survey data collected from 286 manufacturing firms in Finland during 2021 are analysed to examine the relationships between supply chain responsiveness, logistics outsourcing and resilience.
Findings: Firm responsiveness is found to improve resilience, while an increasing level of logistics outsourcing weakens this relationship. Surprisingly, geographic dispersion does not significantly affect supply chain responsiveness.
Research limitations/implications: Limitations of the study include the focus on manufacturing firms in Finland and the reliance on survey data. Future research could explore additional factors influencing resilience and consider a broader range of industries and geographical regions.
Practical implications: The findings offer valuable insights for managers seeking to enhance their firms’ resilience in the face of disruptions. By understanding the importance of responsiveness and the potential drawbacks of excessive logistics outsourcing, managers can make informed decisions to improve their firms’ ability to cope with unexpected challenges.
Originality/value: This research contributes to the understanding of resilience in supply chain disruptions by addressing fundamental questions related to efficiency, responsiveness, control and complexity. By examining the interplay between responsiveness, logistics outsourcing and resilience, the study enriches the understanding of how firms can effectively navigate unexpected challenges.